Towards concessions 2.0 in Central Africa. Managing overlapping rights between industrial concessions and community forestry - (:unkn) unknown (My University, 2016)
In Central Africa, industrial forest concessions and protected areas occupy most of the forested space while community forests are confined to the margins. This separation ignores the reality of land rights and overlapping uses, as well as the need for governance involving different users of the same space. The mapping of local land rights lays the foundation for sharing timber revenues and the development of new economic activities involving industrial operators and communities. A partnership based on rights between industrial operators, communities and other economic operators would lead to a new type of institution of territorial development, which we call Concession 2.0. These redesigned concessions would cohabit and interact with community concessions. The latter would remain forest landscapes offering exclusive rights for autonomous community development.
Keywords: African Research